(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article analyzes the economic geographical characteristics of the impact of a country’s economic development on the lifestyle of the population. The impact of economic growth, trade balance, per capita GDP of countries, and the well-being of the population and economic growth on socio-economic stability was analyzed based on scientific theories of foreign scientists. The impact of import and export volumes on the national economy is also studied, recommendations are made to ensure sustainable development, and in turn, analyses are conducted based on data from the Statistical Agency of Uzbekistan and the World Bank on the economy, highlighting the problem of social inequality between different income groups